Adopsi Inovasi Hasil Riset di IPB University - Ismi Arsilah Rahmawati; Pudji Muljono; Khrishnarini Matindas (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
IPB university is one of the universities that has many innovations, IPB's achievements for 12 years (2008-2019) participating in the 100 plus Indonesian innovation program organized by the Business Innovation Center with support from the Ministry of Research Education, and Culture of the Republic of Indonesia and the Indonesian Institute of Sciences. Higher education is an innovation center that plays a role in the progress of society, providing impact and solutions from the results of research conducted. However, the reality is whether the research carried out provides an effective solution to the community or is just a collection of books that are neatly stored in the library and can only be accessed by certain circles. Quantitative research with correlational survey methods that explain the relationship between variables through hypothesis testing. The results showed that most of the respondents in this study worked as farmers, male gender, productive age, low education and low income. Characteristics that have a real influence on adoption decisions are education, employment and income. The types of innovation and attributes of innovation have a real relationship to the adoption decision and the interpersol communication channel has a real relationship to the innovation adoption decision.